Research in psychotherapy and counselling - Timulak, Ladislav (Sage, 2008)
"This text is based on the book Současny výzkum psychoterapie (Timulak, 2005), which was written in Slovak and the translated into Czech. The text of this book was first translated ... and then edited, revised and updated by me"--Acknowledgements